Mediating incentive use: A time-series assessment of economic development deals in North Carolina - T. William Lester; Nichola Lowe; Allan Freyer (W.E. Upjohn Institute for Employment Research, 2012)
State incentive granting for the purpose of firm retention or recruitment remains highly controversial and is often portrayed as antithetical to long-range economic development planning. This paper uses quasi-experimental methods to measure the impact of state-level economic development incentives on employment growth at the establishment level in North Carolina. Using North Carolina's rich history of strategic planning and sector-based economic development as a backdrop, we develop a theory of sectoral mediation. This enables us to compare the effectiveness of incentives offered in mediated and nonmediated industries and show that when incentives are coupled with sectoral economic development efforts they generate substantially stronger employment effects than at establishments with limited sector-based institutional support.
Keywords: O20; O25; O43; R58; 330; incentives; mediation; employment impacts; firm retention; recruitment